Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1038/s41467-023-39434-0
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for forest condition in Europe based on an international statistical standard

Abstract: Covering 35% of Europe’s land area, forest ecosystems play a crucial role in safeguarding biodiversity and mitigating climate change. Yet, forest degradation continues to undermine key ecosystem services that forests deliver to society. Here we provide a spatially explicit assessment of the condition of forest ecosystems in Europe following a United Nations global statistical standard on ecosystem accounting, adopted in March 2021. We measure forest condition on a scale from 0 to 1, where 0 represents a degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
3
4
0
1
Order By: Relevance
“…While this overall trend is in agreement with the results of Maes et al (2023), who showed that forest conditions across Europe have been even improving from 2000 to 2018, the areas with a prevalence of negative trends can't be ignored. Multiple studies have shown that climate change, by the end of the century, will considerably alter the distribution of European tree species (Mauri et al, 2022) and will be especially threatening for coniferous species (Dyderski et al, 2017), so it becomes crucial to scrutinize any signs of possible range contractions to differentiate between localized phenomena and large-scale shifts.…”
Section: Species' Ranges Assessmentsupporting
confidence: 90%
See 2 more Smart Citations
“…While this overall trend is in agreement with the results of Maes et al (2023), who showed that forest conditions across Europe have been even improving from 2000 to 2018, the areas with a prevalence of negative trends can't be ignored. Multiple studies have shown that climate change, by the end of the century, will considerably alter the distribution of European tree species (Mauri et al, 2022) and will be especially threatening for coniferous species (Dyderski et al, 2017), so it becomes crucial to scrutinize any signs of possible range contractions to differentiate between localized phenomena and large-scale shifts.…”
Section: Species' Ranges Assessmentsupporting
confidence: 90%
“…These results align with a long list of studies assessing either stress or decline for the two species in those areas (Aguadé et al, 2015;Kolář et al, 2017;Rigling et al, 2013;Sedmáková et al, 2019). In contrast, the negative trends hot spots in the moderate (40-50%) range found in the northernmost part of Scandinavia for the same two species align with the results of Maes et al (2023), which indicate a general reduction in ecosystem productivity (NDVI) and soil organic carbon (SOC) in the area rather than a species-specific issue. Hot spots for Scots pine extend further in the northern part of Finland, while spruce stays stable in the area: both trends have been confirmed by a tree-ring analysis conducted by Mäkinen et al (2022) on the data from the last finnish National Forest Inventory (NFI), which found a declining trend for Scots pine especially in sites with mineral soils and in peatlands.…”
Section: Species' Ranges Assessmentsupporting
confidence: 84%
See 1 more Smart Citation
“…These results align with a long list of studies assessing either stress or decline for the two species in those areas (Aguadé et al, 2015;Kolář et al, 2017;Rigling et al, 2013;Sedmáková et al, 2019). In contrast, the negative trends hot spots in the moderate (40-50%) range found in the northernmost part of Scandinavia for the same two species align with the results of Maes et al (2023), which indicate a general reduction in ecosystem productivity (NDVI) and soil organic carbon (SOC) in the area rather than a species-specific issue. Hot spots for Scots pine extend further in the northern part of Finland, while spruce stays stable in the area: both trends have been confirmed by a tree-ring analysis conducted by Mäkinen et al (2022) on the data from the last Finnish NFI, which found a declining trend for Scots pine especially in sites with mineral soils and in peatlands.…”
Section: Species' Ranges Assessmentsupporting
confidence: 84%
“…The LM model has been used extensively to assess land cover composition at various scales to map and analyze landscape patterns [7][8][9][10], plant invasions [11], forest area changes [10,12], and identification of candidate areas for ecological restoration [13]. It has been employed in European ecosystem assessments [14,15], the assessment of green infrastructure of European cities [16], in the United States Resource Planning Act (RPA) forest assessments [17,18] and was recommended as the primary indicator of landscape pattern by the "The H. John Heinz III Center for Science, Economics and the Environment" [19]. Such research and applications have emphasized the well-established concepts that landscape pattern is scale-dependent and that a multi-scale approach is required if the goal is to inform a variety of management and policy questions in a consistent way [20,21].…”
Section: Introductionmentioning
confidence: 99%